Dynamic catalytic adsorptive desulfurization of real diesel over ultra‐stable and low‐cost silica gel‐supported TiO2. Issue 6 (3rd January 2018) - Ren, Xiaoling; Liu, Zewei; Dong, Lei; Miao, Guang; Liao, Neng; Li, Zhong; Xiao, Jing
Abstract : To develop dynamic ultra‐deep catalytic adsorptive desulfurization (CADS) of real diesel using ultra‐stable and low‐cost silica gel‐supported TiO2 is the aim of the work. A two‐stage dynamic breakthrough model was built to describe the CADS process, varied with H/R ratio and O/S ratio. The desulfurization capacity reached 1.3 mg‐S/g‐A at the breakthrough concentration of 5 ppm‐S. Various types of silica gel were screened as the substrate for TiO2, and the textural/acidic properties and CADS capacity were correlated in high relevancy. The effectiveness of diverse oxidants on CADS and the oxidation path were elucidated via combined experiment/simulation. Adsorption enthalpy derived from fitted isotherm data was calculated as 33.4 kJ/mol. The TiO2 /silica gel‐based sorbent demonstrated remarkable recyclability/stability in 10 cycles. An effective and economic route to eliminate the trace amount of stubborn sulfur compounds in low‐sulfur diesel is provided, which can be potentially implemented as the final polishing step for ultra‐clean diesel production. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2146–2159, 2018